ANALISIS SALURAN DISTRIBUSI DAN MARGIN PADA PUPUK UREA BERSUBSIDI (STUDI KASUS PADA DI DESA DAME, KECAMATAN DOLOK MASIHUL) - Yuristia, S.P., M.Si, Rahmi (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2022)
Dolok Masihul is one of the sub-districts in Serdang Bedagai Regency. The fertilizer distribution system in this region is still not in accordance with the policies set by the government. The amount of subsidized fertilizer that farmers in this village should receive is 25 kg, but in reality the subsidized fertilizer that reaches farmers is only 3 kg. This is not appropriate because the fertilizer that farmers need for their rice is still very low, so farmers are required to buy back the fertilizer which should be subsidized. The research aims to describe fertilizer distribution channels and margins on subsidized urea fertilizer. The research results show thatProducers consist of PT. Pupuk Sriwijaya as a producer of Urea Fertilizer is then distributed to distributors, namely the Urea Fertilizer Distributor by PT Tani Mulia. PT Tani Mulia acts as the second channel which receives fertilizer from the Pusri warehouse and distributes the fertilizer to all retailers so that it reaches the final consumer, namely farmers. Then each distributor distributes the subsidized fertilizer to retailers. The type of fertilizer distributed to farmers is Urea fertilizer. Once at the retail agent level, it will then be distributed to the Farmer Group level, for the number of farmer groups that receive subsidized fertilizer from each village, namely 12 farmer groups. At the next level the fertilizer will be distributed to the final consumers, namely farmers. The marketing costs incurred by distributors of subsidized urea fertilizer are IDR 92/Kg. Meanwhile, the marketing costs incurred by retailers of subsidized urea fertilizer are IDR 93/Kg. Share Margin for subsidized urea fertilizer distributors is 4.4% and Share Margin for subsidized urea fertilizer retailers is 5.19%